2020
DOI: 10.3390/s20133760
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Development to Examine Collaborative IoT Supply Chain System Underlying Privacy and Security Levels and Perspective Powering through Proactive Blockchain

Abstract: Undoubtedly, the supply chain management (SCM) system is an important part of many organizations worldwide; over time, the technologies used to manage a supply chain ecosystem have, therefore, a great impact on businesses’ effectiveness. Among others, numerous developments have been made that targeted to have robust supply chain systems to efficiently manage the growing demands of various supplies, considering the underlying requirements and main challenges such as scalability, specifically privacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 61 publications
(138 reference statements)
3
17
0
Order By: Relevance
“…That is, differences in the impacts of indicators on sustainability are different among major FSC participants in the WB region during the COVID-19 pandemic. The finding confirms the results of previous research on the significance of differences between business activities within the FSC [33][34][35][36][37][38].…”
Section: Research Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…That is, differences in the impacts of indicators on sustainability are different among major FSC participants in the WB region during the COVID-19 pandemic. The finding confirms the results of previous research on the significance of differences between business activities within the FSC [33][34][35][36][37][38].…”
Section: Research Resultssupporting
confidence: 90%
“…The conducted research shows a different influence of the given indicators on the food placement among FSC participants. This is also an expected result, given recent research [33][34][35][36][37][38]41] that highlights the strong correlation of differences in FSC business sectors with placement efficiency. In this context, energy consumption comes to the fore in production, which has no statistically significant impact in retail, but rather the changing needs of consumers.…”
Section: Discussionsupporting
confidence: 75%
“…They identified that the higher investment cost, lack of trained workers in implementing and operating the technologies, especially IoT, lack of modern infrastructure to support industry 4.0 are the critical barriers in incorporating these technologies in supply chains. Similarly, the previous studies also reported the same results regarding the acceptance and implementation of emerging technologies in supply chains Majeed and Rupasinghe, 2017;Oláh et al, 2020;Rehman et al, 2020;Shahzad et al, 2020). Yadav et al (2020) also reported the lack of government regulations and lack of trust among the agro-stakeholders as the critical barriers to implementing blockchain technology.…”
Section: Ro4 Barriers In Implementing the Emerging Technologiessupporting
confidence: 58%
“…is cluster is thus related to digital signcryption. Digital signature encryption has been investigated on algorithms, such as the elliptic curve digitalsignature algorithm, digital-signature mobile applications, and digital-signature systems, to achieve document integrity and provide nonrepudiation security services in a distributed computing environment [103][104][105][106][107]. It is also important to satisfy reliability and confidentiality requirements of crowdsourced data [108,109].…”
Section: Keyword Clustering and Evolution Of Research On Iotmentioning
confidence: 99%
“…Topic 10 is related to the adoption of blockchain in smart-IoT applications, such as smart contracts, smart inventory management, smart e-commerce, and smart shopping systems [140,155,[267][268][269][270][271][272][273][274][275][276][277][278][279].…”
Section: Identification Of Topics In Iot Securitymentioning
confidence: 99%